The reality of quality in the SAI reports: Applied research in the Federal Board of Supreme Audit (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The research aims to shed light on the role of SAIs and the nature of their work, with the definition of the concept of quality reports and to clarify the reality of quality in the FBSA reports, the researchers reached to conclusions, including: The quality of the SAI reports is a requirement seeks to achieve any regulatory system in order to develop audit work output of the form in which its impact is reflected positively on the performance of the entities controlled, and researchers gave a set of recommendations, including: the need to increase community awareness of the importance of the FBSA Supervisory reports through conferences, seminars and workshops and that FBSA to follow-up reports, and check the quality continuously to the fact that the regulatory reports represent the product of his work the oversight exercised.